Assessment of Business Process Alignment to IT Business Objectives - Vincentius Octavianus; Harryston Nagata; Johanes Fernandes Andry (LPPM Universitas Dian Nuswantoro, 2018)
Manufacturing company is a company engaged in the manufacture of household appliances such as plastic houseware, bushels food, rice bucket, and so forth. the company has implemented an application in running the business process of goods sales and goods (inventory). However, there is a problem in the application that is used to support the activity in the business process that is the discrepancy with the needs of users of the application and will be an assessment of the business process. Therefore, the authors take this topic. The purpose of this study is to determine the deficiencies that occur in the company, so the author can provide recommendations to the company about what should be improved. The research method used in this research is qualitative research and data obtained from the interview. In this study, the assessment of the business process Manufacturing company using COBIT 4.1 and Balanced Scorecard (BSC). This research focuses on PO3 (Determine Technological Direction) domains, PO4 (Communications Management Aims and Direction), PO8 (Manage Quality), and AI4 (Enable Operation and Use). From the research that has been done, the results show that this company has not reached the expected maturity level.